1999
DOI: 10.1016/s0960-9822(00)80116-5
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-induced mitogenesis is mediated by casein kinase 2 and nucleolin

Abstract: We conclude that in human vascular smooth muscle cells, uPA induces the formation and activation of a newly identified signaling complex comprising uPAR, nucleolin, and casein kinase 2, that is responsible for the uPA-related mitogenic response. The complex is not a unique feature of vascular smooth muscle cells, as it was also found in other uPAR-expressing cell types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 54 publications
(75 reference statements)
3
65
0
Order By: Relevance
“…Other investigators have shown that nucleolin can be found on the cell surface (24,(27)(28)(29)(30)(31)(32)(33)(34). Nucleolin can interact with the IKVAV site of laminin, which is a major component of basement membranes (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have shown that nucleolin can be found on the cell surface (24,(27)(28)(29)(30)(31)(32)(33)(34). Nucleolin can interact with the IKVAV site of laminin, which is a major component of basement membranes (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Later, Dumler et al (18) demonstrated co-internalization of the uPAR⅐nucleolin complex inside the cell, which emphasizes the possibility of nuclear translocation of uPAR. We show that IR-induced overexpression of uPAR leads to uPAR translocation in the nucleus and its association with different transcription factors that may facilitate maintenance of stemness.…”
mentioning
confidence: 97%
“…In addition, nucleolin has been implicated, directly or indirectly, in other roles including nuclear matrix structure (19), DNA replication (20), cytokinesis and nuclear division (21), and as a nucleic acid helicase (12,22). There have been numerous reports describing the presence of nucleolin in the plasma membrane of cells (9,(23)(24)(25)(26)(27)(28), suggesting a further * This work was supported by the Department of Defense Prostate Cancer Initiative, the National Institutes of Health, and the Commonwealth of Kentucky Research Challenge Trust. The costs of publication of this article were defrayed in part by the payment of page charges.…”
mentioning
confidence: 99%